Impact of air pollution in Mymensingh city of Bangladesh: focusing peoples’ perception (Progressive Agriculture, 2021)
The present study was conducted to investigate the impact of air pollution in some selected areas of Mymensingh city. The relationship between independent variables (age, educational qualification, family size and communication exposure) with the basic idea and impact of air pollution (dependent variable) was investigated in this study. To conduct the study, two hundred (200) respondents were selected randomly from four study sites under Mymensingh city. Pearson's product-moment correlation coefficients were analyzed to examine the relationship between the concerned variables. The findings revealed that 87.5% people have basic idea and 12.5% people have no idea about air pollution. About half (46%) of the peoples had high impact, 34% had medium and 20% had low impact because of air pollution. Out of four independent variables, three variables such as educational qualification and communication exposure had positive and significant relationship, age had negative but significant relationship and family size had non-significant relationship with their perception and awareness of air pollution. Further assessment on different air pollutants in the study area may explore the original status of air pollution and their impact on environment as well as on livelihood.Progressive Agriculture 31 (3): 154-163, 2020